2014
DOI: 10.1371/journal.pone.0103743
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Oxidation of Cholesterol: Properties and Functional Effects of Cholestenone in Cell Membranes

Abstract: Bacterial cholesterol oxidase is commonly used as an experimental tool to reduce cellular cholesterol content. That the treatment also generates the poorly degradable metabolite 4-cholesten-3-one (cholestenone) has received less attention. Here, we investigated the membrane partitioning of cholestenone using simulations and cell biological experiments and assessed the functional effects of cholestenone in human cells. Atomistic simulations predicted that cholestenone reduces membrane order, undergoes faster fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 52 publications
1
51
0
Order By: Relevance
“…S2b), an important indicator of condensation/ordering of lipids. [8-10] Furthermore, cholesterol preferences, order parameters, and heights of the saturated DPPC and the unsaturated DLiPC lipids are all comparable among the different sterol systems (Fig. 1d-f).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…S2b), an important indicator of condensation/ordering of lipids. [8-10] Furthermore, cholesterol preferences, order parameters, and heights of the saturated DPPC and the unsaturated DLiPC lipids are all comparable among the different sterol systems (Fig. 1d-f).…”
Section: Resultsmentioning
confidence: 86%
“…Cholesterol consists of a 3b-hydroxyl group, a rigid sterol ring, and a flexible aliphatic chain. Cholesterol's ability to enhance ordering of lipid hydrocarbon chains, or its condensing effect [5][6][7], was suggested to arise from the tilting of the sterol ring [8][9][10]. Other studies showed that the flat a-face of cholesterol preferentially interacts with saturated tails of high-melting lipids while the rough b-face has no preference for tail unsaturation [5,6,11,12].…”
Section: Edited By Sandro Sonninomentioning
confidence: 99%
See 1 more Smart Citation
“…As compared to cholesterol, CHS is a more water-soluble cholesterol ester and is widely used in structural biology and biophysical studies as a cholesterol analogue (Zocher et al, 2012; Loll, 2014). Oxysterols, on the other hand, are derivatives of cholesterol with additional oxygen-containing substitutions at different positions of cholesterol (Olkkonen and Hynynen, 2009; Kulig et al, 2015a; Neuvonen et al, 2014). Due to the structural similarities with cholesterol, these analogues mimic cholesterol as to the effects on membrane properties (e.g., increasing bilayer order and thickness), although to different extents (Figure 2—figure supplement 6) (Kulig et al, 2015a, 2015b).…”
Section: Resultsmentioning
confidence: 99%
“…Neuvonen et al studied effect of cholesterol oxidation upon membrane properties and cellular functions by simulation and cellular experiments [56]. Cholesterol oxidase or MβCD-loaded with steroid was used to increase 4-cholesten-3-one and decrease cholesterol levels in human dermal fibroblasts.…”
Section: Studies In Eukaryotic Cell Plasma Membranes Using Sterol-modmentioning
confidence: 99%